Funds of the Central National Archives of Supreme Authorities and Government of Ukraine as a source of the research of USSR Peopleʼs Commissariat of Education in the sphere of Higher Education (1920s) - Mazurenok, Maryna (Pedagogical Discourse, 2013)
The article describes the Funds of the Central National Archives of Supreme Authorities and Government of Ukraine, which revealed the activities of USSR Peopleʼs Commissariat of Education in the sphere of higher education in the 1920s. Archival sources that contain information on the reorganization of the system of higher education, implementation of «ukrainianization» policy in the educational process of universities are analysed in it. The author reveals the content of archival documents which highlighted the problem of proletarianization of higher educational institutions and the socio-academic checks of students according to their background.